Expectation and Quality Perception of the Passengers towards the Bus Service Provision at the Southern Bus Termina - Nilpuang, Sunan (Journal of Management Science Nakhon Pathom Rajabhat University, 2018)
The study entitled “Expectation and Quality Perception of Passengers towards the Bus Service Provision at the Southern Bus Terminal aims to 1) study expectation towards quality of the bus service provision at the southern bus terminal, and 2) study the quality perception of the passengers towards the bus service provision at the southern bus terminal. A questionnaire was used in data collection from those 397 passengers who are served at the southern bus terminal while Frequency, Percentage, Means, Standard Deviation, Pearson Correlation Coefficient Analysis, t-Test, One-Way Analysis of Variance, and Pearson Correlation Coefficient Analysis were utilized in data analysis. It is revealed that the expectation level towards the quality of the bus service provision at the southern bus terminal is at the high level (Mean = 3.65). The expectations evaluated in the first three orders are the formation of confidence in travelling with the buses (Mean = 3.82), the adjustment of the bus fare to match with the cost of living (Mean = 3.78), the suitability of the fare and the service quality (Mean = 3.67) respectively. The perception towards the service quality of the bus service provision at the southern bus terminal is at the high level (Mean = 3.75). The perception evaluated in the first three orders are the safety from the accidents in travelling all the way with the buses (Mean = 4.22), the buses in a good condition (Mean = 4.04), and the safety from the crime all the way of the travelling (Mean = 3.79) respectively. The individual characteristics influence the expectation in all dimensions except that on the income per month which is found to be statistically significant indifferent. Besides, the individual characteristics influence the perception on the inside of the buses and that on the service provision in all dimensions except the factor on sex which is found to be statistically significant indifferent. The expectation towards the service quality of the passengers relates to the perception on the service provision at the highest level (r=0.76) followed by the relationship with the inside of the bus (r=0.71), and with the service provided on the way of travelling (r=0.63) respectively. Article history : Accepted 15 October 2014 SIMILARITY INDEX = 4.95